Influence of the Somatic Rubber Hand Illusion on Maximum Grip Aperture. Issue 1 (2nd January 2023) - Brusa, Federico; Erden, Mustafa Suphi; Sedda, Anna
Abstract: The classic rubber hand illusion (RHI), based on visual, proprioceptive, and tactile feedback, can affect actions. However, it is not known whether these effects still occur if the paradigm is administered without visual feedback. In this study, we used the somatic RHI to test in thirty-two healthy individuals whether the incorporation of the rubber hand based on proprioceptive and tactile information only is sufficient to generate changes in actions. We measured maximum grip aperture (GA) changes towards a target and associated brain activations within the dorsal stream before and after the somatic RHI. Behavioural and neuroimaging data do not support an effect on maximum GA when the RHI is based on proprioceptive and tactile information only.